Construction and mental mechanisms for learning about the exponential function in a school setting - Cordova Cornejo, Víctor Enrique (2024)
[Objective] The objective of this study was to examine, in the light of the APOS theory (action, process, object, and schema), the results produced by secondary school students when addressing 11 items related to the exponential function. [Methodology] The approach was qualitative, using content analysis. The sample consisted of 15 students between 15 and 18 years old, chosen in a non-probabilistic way to obtain the greatest amount of information. Based upon the theory, an instrument was designed which consisted of a hypothetical genetic decomposition of the concept of exponential function as a cognitive object, according to structures (action, process, object and schema) and mental mechanisms (interiorization, coordination, encapsulation, decapsulation, and investment), to interpret the mental construct that students create about the function being studied, based on its historical epistemological development, its presentation in school textbooks and the experience of the researcher. [Results] At the level of results, it was found that 13 students showed an action conception of the function being studied and 2 students built the concept at the process level. [Conclusion] Students most often built the concept of an exponential function at the action level, that is, everything related to repetitive and mechanical processes with powers, image calculation, graphic representation, solution of exponential equations; some students even responded to the items without explicitly performing all the steps required for their resolution. These results demonstrated the absence of a mental process related to the exponential function and its consequent encapsulation into an exponential function object.